Preliminary survey of radioactivity level in Thai medicinal herb plants - C. Kranrod (2018)
© Published under licence by IOP Publishing Ltd. In this research, the natural radioactivity concentrations and their respective annual effective dose of the naturally occurring radionuclides 226 Ra, 228 Ra and 40 K in selected medicinal herb plants were investigated. Seven kinds of popular Thai medicinal herb plants had been studied: turmeric, ginger, safflower, moringa, gotu kola, garlic and alexandria senna. The radiological risk associated with the use of these medicinal plants was assessed. The activity concentrations of 226 Ra, 228 Ra and 40 K were determined using the gamma-ray spectrometry technique. The radioactivity concentrations were found to range from less than 0.20 to 6.67 Bqkg -1 for 226 Ra, less than 0.10 to 9.69 Bqkg -1 for 228 Ra, and from 159.42 to 1216.25 Bqkg -1 for 40 K. Gotu kola showed the highest activity concentrations of 226 Ra and 228 Ra, while ginger showed the highest activity concentration of 40 K. The total annual effective dose due to ingestion of these herb plants were found to range from 0.0028 to 0.0097 mSvy -1 with an average value of 0.0060±0.0001 mSvy -1 . The results conclude that the Thai medicinal herb plants samples from this research are considered safe in terms of the radiological hazard.